Sepsis and post-sepsis syndrome: a multisystem challenge requiring comprehensive care and management—a review - Torres, Jhan Sebastian Saavedra; Tamayo-Giraldo, Francisco Javier; Bejarano-Zuleta, Alejandro; Nati-Castillo, H. A.; Quintero, Diego A.; Ospina-Mejía, M. J.; Salazar-Santoliva, Camila; Suárez-Sangucho, Isaac; Ortiz-Prado, Esteban; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2025)
Sepsis, a medical emergency with high mortality rates, demands comprehensive care spanning from early identification to patient rehabilitation. The sepsis survival chain encompasses early recognition, severity assessment, activation of emergency services, initial antimicrobial therapy, hemodynamic stabilization, and integrated rehabilitation. These interconnected steps are critical to reducing morbidity and mortality. Despite advancements in international guidelines, adherence remains limited, contributing to a significant disease burden. Beyond its acute phase, post-sepsis syndrome (PSS) is characterized by long-term immune dysregulation, chronic inflammation, and metabolic dysfunction, predisposing survivors to recurrent infections, cardiovascular disease, and neurocognitive decline. Mitochondrial dysfunction and epigenetic modifications play a central role in prolonged immunosuppression, impairing adaptive and innate immune responses. Sepsis-induced organ dysfunction impacts multiple systems, including the brain, heart, and kidneys. In the brain, it is associated with neuroinflammation, blood-brain barrier dysfunction, and the accumulation of neurotoxic proteins, leading to acute and chronic cognitive impairment. Myocardial dysfunction involves inflammatory mediators such as TNF-α and IL-6, while sepsis-associated acute kidney injury (SA-AKI) arises from hypoperfusion and inflammation, heightening the risk of progression to chronic kidney disease. Additionally, immune alterations such as neutrophil dysfunction, continuous platelet activation, and suppressed antitumoral responses contribute to increased infection risk and long-term complications. Timely and targeted interventions, including antimicrobial therapy, cytokine modulation, immune restoration, metabolic support, and structured rehabilitation strategies, are pivotal for improving outcomes. However, financial and infrastructural limitations in low-resource settings pose significant barriers to effective sepsis management. Precision medicine, AI-driven early warning systems, and optimized referral networks can enhance early detection and personalized treatments. Promoting public and professional awareness of sepsis, strengthening multidisciplinary post-sepsis care, and integrating long-term follow-up programs are imperative priorities for reducing mortality and improving the quality of life in sepsis survivors.